Neurosteroid modulation of N-methyl-D-aspartate receptors: molecular mechanism and behavioral effects - Korinek, Miloslav; Kapras, Vojtech; Vyklicky, Vojtech; Adamusova, Eva; Borovska, Jirina; Vales, Karel; Stuchlik, Ales; Horak, Martin; Chodounska, Hana; Vyklicky, Ladislav (Steroids, 2011)
Glutamate is the main neurotransmitter released at synapses in the central nervous system of vertebrates. Its excitatory role is mediated through activation of specific glutamatergic ionotropic receptors, among which the N-methyl-D-aspartate (NMDA) receptor subtype has attracted considerable attention in recent years. Substantial progress has been made in elucidating the roles these receptors play under physiological and pathological conditions and in our understanding of the functional, structural, and pharmacological properties of NMDA receptors. Many pharmacological compounds have been identified that affect the activity of NMDA receptors, including neurosteroids. This review summarizes our knowledge about molecular mechanisms underlying the neurosteroid action at NMDA receptors as well as about the action of neurosteroids in animal models of human diseases.
Keywords: chování; Disease; Steroids; Neurotransmitter Agents; nemoc; neurotransmiterové látky; steroidy; receptory GABA; Animals; lidé; Receptors, GABA; Receptors, N-Methyl-D-Aspartate; receptory N-methyl-D-aspartátu; Humans; zvířata; Behavior